Calidad del cuidado de enfermería y satisfacción percibida por el paciente. Hospital Regional Docente-2019 - Ordoñez Orbegozo, Ruth Noemí (2019)
The present quantitative, descriptive, correlational and cross-sectional research was carried out with the goal to establish the relation between the quality of nursing care and the level of satisfaction perceived by the patient, Regional Teaching Hospital - 2019. The sample is made up of 111 patients hospitalized in the surgery service A. The instruments used are two: Scale of the quality of nursing care and the scale of patient satisfaction. The results obtained was: 93.7 % are satisfied and 6.3% are not satisfied, about quality of nursing care, 78.4% of patients perceived the nursing care as good, 15.3% as regular and 1.5% as bad. There is a highly significant correlation between both variables with a probability of 0.000.